Local Wisdom of Kandri People in Conserving Water Resources Gunungpati Semarang - Anam, Chairul; Banowati, Eva; Juhadi, Juhadi (JESS (Journal of Educational Social Studies), 2018)
The availability of water in Gunungpati Subdistrict and its surroundings is generally declining, while the need for water continues to increase, so that conflicts over water use will occur. But in Kandri Village, there are springs that have large discharge and are maintained by the presence of local wisdom of the local community. The technique of data collection techniques interviews, observation, and documentation. Data analysis using qualitative description. The results showed that the public perception towards spring, namely spring water as God-given gift, supernatural creatures, dwelling place of haunted, Holy places, and bring blessings to the citizens. Other forms of local wisdom consists of events nyadran kali conducted on Thursday kliwon Jumadil Akhir month of Islamic calendar, Matirto Suci Dewi Kandri dance a meaningful phrasing gratitude and norms in the form of recommendations as well as the prohibition of should not be denounced water, kitchen appliances, washing is prohibited should not take water directly from springs and if want to use must request a permit a meaningful tribute to against springs and nature around, protect the eyes from water pollution, keeping the output water sustainability and avoid the use of undue hardship. Efforts to preserve local wisdom, namely carrying out events nyadran kali on a regular basis, the modification of ritual nyadran kali are adjusted with the times, strengthening the community spirit and tradition of the religion, and make the village Kandri village Tour. This research is expected to provide information on knowledge of spring water conservation based on local wisdom to the community.